A Review of Recycled Asphalt In Rigid Pavement - Supar, Khairi; Kaamin, Masiri; Ahmad, Hilton; Mohammad, Hairuddin (Multidisciplinary Applied Research and Innovation, 2021)
Recycled Asphalt Pavement (RAP) is designed as another of the construction wastes produced by infrastructure and reconstruction sector. RAP is a product of current surface removal where the reconstruction takes place. The evolution of road construction in Malaysia has increased the waste of asphalt aggregate but the uses of recycled asphalt bitumen as one of the materials in road construction in Malaysia was said to be very effective. The uses of recycled asphalt pavement (RAP) in road work lead to various quality of asphalt and able to support high loading if applicable proportion with maximum percentage in the design mixture. In create a new construction and insulation material, the modification needed in concrete mixture with added such as an anionic bitumen emulsion. RAP was mixed in a rigid pavement mixture to replace aggregate. By using recycled bituminous in rigid pavement as road construction, this new mixture can be absorded more vibration from vehicles on the road as rigid pavement. It can be extended work in the future with a variation of percentage of the mixture in order to produce maximum strength.